An overview of lignin pathways of valorization: from isolation to refining and conversion into value‑added products - Martins, M. Margarida (2022)
ABSTRACT: The increasing demand for greener and sustainable alternatives to fossil-derived fuels, chemicals, and materials has attracted huge attention to lignin, the largest renewable source of aromatic building blocks on earth. This natural polymer accounts for 15 to 40% of all lignocellulosic biomass. As such, in the pulp and paper industries, for example, huge amounts of lignin are produced worldwide. However, most applications for these lignins are of low value, such as their burning for energy. Furthermore, with the introduction of second-generation ethanol biorefineries, the overall lignin production increased. To attain a circular bio-based economy, all side-streams of lignocellulosic biomass and, particularly, lignin should be valorized to as high of a value as possible. Lignin's rich structure has allowed achieving various high-value products over the years, not only in the production of biofuels but also regarding chemicals and materials. The present paper addresses a broad vision of the several stages of lignin valorization, from the isolation of lignin through pre-treatments of lignocellulosic biomass and the current industrial lignin production to fractionation methodologies that provide homogeneous lignins more adequate for valorization and the conversion of lignin into value-added products via chemical and biological routes.